Projections - Brito, Claudio da Rocha (2012)
The academic community dedicated to the search of science of communication and arts can count with an international forum for the discussions about communication and arts research. It is the WCCA’2013 - VI World Congress on Communication and Arts organized by COPEC ¾ Science and Education Research Council and promoted by WCCA ¾ World Council on Communication and Arts. It happens for the first time in Australia. The theme of this edition Projections” has brought researchers and professionals of these areas to participate at the conference showing their interesting scientific works.